The Shocking Truth: Why Renewable Energy in Maluriwu Village is Falling to Meet Public Needs - Likuwatan Werang, Nicolaus Petrus; Rizki, Mia; Yolandasari, Priscilia (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
The challenges of renewable energy at the village level leave problems that are not yet optimal in practice to facilitate public needs, especially in Maluriwu Village, Sikka Regency, East Nusa Tenggara. Although the provision of renewable energy supports the provision of public services, the facts are not significant. Furthermore, the method adopted is descriptive qualitative to understand the problem of renewable energy as a means of providing public needs at the village level. Data were obtained through interviews by identifying participants competent in providing information related to the research theme. The findings reveal that there is a gap between community participation and community expectations when planning programs. There is a lack of community representation in the discussion forums that were initiated, where there are concerns and dissatisfaction with the program promised by the government. In general, these findings require special attention from the government to village residents to provide public services through appropriate policies.